2016
DOI: 10.1007/978-3-319-42070-7_24
|View full text |Cite
|
Sign up to set email alerts
|

Different Roles in Leadership Styles in Modern Organization

Abstract: Today´s rapidly changing world has forced leaders to change their leadership styles aligned to the current situation faster than ever. What kind of leadership style should be utilized in modern expert organization? What are leaders´ own experiences and can leadership styles somehow been assessed? What have scholars founded regarding leadership styles? This paper examines different situational leadership approaches in order to reveal literature based ontology of leadership styles. Ontology includes leadership s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
2
7
0
1
Order By: Relevance
“…Furthermore, one of our findings was that the description of Lean thinking was unclear in the majority of the studies, and there were few if any definitions of features that would differentiate Lean leadership and management from any other managerial or improvement settings. This is in accordance with a previous review which concluded that by reviewing the literature, everything it seems may be termed Lean (34). Nevertheless, by analyzing the characteristics of managerial dimensions, we were still unable to obtain evidence as to whether Lean thinking had been adapted successfully in the studied organizations and whether the targets and goals had been reached or not; it was also not possible to determine the impact of the managerial function in the process of adaptation to Lean thinking.…”
Section: Conclusion and Practical Implicationssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, one of our findings was that the description of Lean thinking was unclear in the majority of the studies, and there were few if any definitions of features that would differentiate Lean leadership and management from any other managerial or improvement settings. This is in accordance with a previous review which concluded that by reviewing the literature, everything it seems may be termed Lean (34). Nevertheless, by analyzing the characteristics of managerial dimensions, we were still unable to obtain evidence as to whether Lean thinking had been adapted successfully in the studied organizations and whether the targets and goals had been reached or not; it was also not possible to determine the impact of the managerial function in the process of adaptation to Lean thinking.…”
Section: Conclusion and Practical Implicationssupporting
confidence: 93%
“…The aim of this study was to review and analyze recent literature regarding Lean leadership and management, and to identify the characteristics of leadership and management that are associated with successful Lean thinking adaptation in health care. In addition, we tested the concept of the windshield (31)(32)(33)(34) to analyze the skills and capabilities of Lean leadership and management that were described in the original studies, as to present a comprehensive overview of the managerial traits that are important for achieving successful Lean thinking in health care. Vanharanta describes that the management windshield metaphor is built from three different viewpoints: time, leadership and management.…”
mentioning
confidence: 99%
“…An assumption in this study is that the individual who has a broad repertoire of interventions/behaviours has better opportunities to succeed in management positions that require group leadership skills than the individual relying on a one-sided pattern of interventions, no matter the situation. This assumption is in-line with Reunanen and Kaitonen ( 2016 ), who argue that leaders need different styles in their functional roles.…”
Section: Introductionsupporting
confidence: 82%
“…The following steps aim to revise and develop the model to a prototype for team leader assessment and develop it to the first version of a completed intervention inventory, test–retest, item analysis, variable correlation, factor analysis, and validation against personality test or inventories. The best practise guide for developing leadership scale, according to the paper of Reunanen and Kaitonen ( 2016 ), is adapted from DeVellis ( 2016 ) elements for broad-scale development over four key elements: generating theory, item development, content adequacy, and empirical evaluation. These elements will be followed in developing this behaviour inventory and in a later step by completing this inventory by the leaders thinking and feeling when unexpected events arise in group meetings .…”
Section: Discussionmentioning
confidence: 99%
“…In the organization, a leader is one who can control factors such as: individual rights, working conditions, policies of the organization, identification, progress, and responsibility. In fact, how the leader can control these factors and how motivates the staff, reflects if the leader is effective (Reunanen and Kaitonen, 2017). That is why it is expected that the person who is the leader of an organization necessarily perform all the duties of a manager.…”
Section: Introductionmentioning
confidence: 99%